Preliminary Survey on the Impact of Schmallenberg Virus on Sheep Flocks in South of Belgium. Issue 5 (7th January 2013) - Saegerman, C.; Martinelle, L.; Dal Pozzo, F.; Kirschvink, N.
Summary Between late February and May 2012, a preliminary anonym survey was conducted among sheep farmers in south of Belgium in order to contribute to future estimations of the economic losses caused by Schmallenberg virus (SBV). Based on clinical signs consistent with SBV infection, this survey involved 13 meat sheep flocks considered as positive flocks with subsequent SBV detection by RT‐qPCR [SBV‐positive flocks (PF); total of 961 animals], and 13 meat sheep flocks considered as negative flocks (NF; total of 331 animals). These preliminary results indicated several significant characteristics that were more present in PF than in NF. These include an increased rate of abortions (6.7% in PF versus 3.2% in NF), of lambs born at term but presenting malformations (10.1% in PF versus 2.0% in NF) and of dystocia (10.1% in PF versus 3.4% in NF). Lamb mortality during the first week of life was reported more frequently in PF (8 of 13 PF, 61.5%) than in NF (1 of 13 NF, 7.7%). In PF, the observed prolificacy rate was 2‐fold lower (93%) than expected (186%). The implementation of a survey at larger scale, including a high number of breeders, is necessary to allow a more detailed analysis of the SBV impact in the sheep sector.